Evolutionary Divergence of the Novel Staphylococcal Species Staphylococcus argenteus - Wu, Shi; Pang, Rui; Huang, Jiahui; Zhang, Feng; Cai, Zhihe; Zhang, Jumei; Chen, Moutong; Xue, Liang; Gu, Qihui; Wang, Juan; Ding, Yu; Wan, Qiang; et al. (Frontiers in Microbiology, 2021)
Currently, invasive infections caused by Staphylococcus argenteus, which is a recently named staphylococcal species, are increasingly reported worldwide. However, only a few genomic studies of S. argenteus have offered comprehensive information regarding its genetic diversity, epidemiological characteristics, antimicrobial resistance genes (ARGs), virulence genes and other profiles. Here, we describe a comparative genomic analysis by population structure, pangenome, panmobilome, region-specific accessory genes confer an adaptive advantage in 153 S. argenteus strains which comprised 24 strains sequenced in this study and 129 strains whose genome sequences were available from GenBank. As a result, the population of S. argenteus comprised seven genetically distinct clades, including two major clades (C1 and C2), with distinct isolation source patterns. Pangenome analysis revealed that S. argenteus has an open pangenome composed of 7,319 genes and a core genome composed of 1,508 genes. We further determined the distributions of 75 virulence factors (VFs) and 30 known ARGs and identified at least four types of plasmids and 93 complete or partial putative prophages. It indicate that S. argenteus may show a similar level of pathogenicity to that of S. aureus. This study also provides insights into the evolutionary divergence of this pathogen, indicating that the geographical distribution was a potential driving force behind the evolutionary divergence of S. argenteus. The preferential horizontal acquisition of particular elements, such as SCCmec elements and plasmids, was observed in specific regions, revealing potential gene exchange between S. argenteus strains and local S. aureus strains. Moreover, multiple specific genes related to environmental adaptation were identified in strains isolated from East Asia. However, these findings may help promote our understanding of the evolutionary divergence of this bacterium at a high genetic resolution by providing insights into the epidemiology of S. argenteus and may help combat its spread.